Dampak Natur Manusia Berdosa melalui Munculnya Keterbuaian pada Aspek Penggunaan Bahasa [The Impact of Man's Sinful Nature in The Use of Language] - Jonter Pandapotan Sitorus (Universitas Pelita Harapan, 2020)
The objective of this study is to understand the impact of man’s sinful nature as an inborn trait in humanity. The sinful nature of man becomes more complex in every aspect of his life. The method used in this research is literature study which seeks to analyze relevant bibliographies on several forms of human infatuation as the result of man’s sinful nature. From this study, it can be concluded that there are several forms of sinful human infatuation i.e. infatuation in the aspect of religion and God, in the aspect of technology and culture, and in the aspect of language and its application. But the emphasis here is on the infatuation in the aspect of language usage in the Indonesian context. One reason for this is that most people in our society tends to have greater love and pride in foreign languages. Such attitude in linguistics is known as xenoglosofilia. The impact of this infatuation on foreign languages is a lack of respect for one’s own native language, viewing it as less prestigious compared to other languages.